EFFICACY OF HYPTIS SUAVEOLENS LEAF OILS IN PROTECTING STORED MAIZE AGAINST ADULT MAIZE WEEVIL (Sitophilus zeamais) M - Abdulmalik, B.S.; Abdullahi, N.; Alkali, Z.; Abba, E. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2018)
Laboratory experiment was conducted in the postgraduate laboratory of the Department of Biological sciences, Gombe State University, to test the insecticidal effects of leaf oils of Hyptis Suaveolens (L.). Concentration of 0.1, 0.2, 0.3 and 0.4ml of the leaf oils and 0.1ml of Dichlorvos (treated control) were applied to 20g each of maize grains at three replicate in which five (5) adult Sitophilus zeamais Motschulsky were introduced for adult mortality, emergence, grains weight loss and seed damage. The results showed that the highest (100%) mortality of S. zeamais obtained when 0.4ml was applied after 168hrs of treatment while the least (6.66%) was recorded after 24hrs of treatment at the same concentration. The results also revealed that the highest (1.67±0.00) and (1.33±0.00) for F1 and F2 adult emergence of the weevils were obtained when 0.1ml and 0.2ml was applied, while no adult emergence (0.00±0.00) was recorded at the highest concentration (0.4ml) for both F1 and F2 respectively. The findings of this study showed that the adult mortality and adult emergence of S. zeamais was directly proportional to the concentration of the leaf oils applied. Lowest grain percentage weight loss and seed damage was recorded in 0.4ml grain treatment (0.50% and 8%) respectively. Generally, the efficacy of the leaf oils on the mortality, adult emergence and weight loss and damage of S. zeamais was found to be significantly (p<0.05) different between the test oils and the untreated control. Findings of this study showed that the leaf oil of H. suaveolens was effective in protecting maize grains against S. zeamais infestation in stores. Therefore, more research is recommended on toxicity effect of these plant leaves oil on other insect pests.